Impossible Empathy: The Non-Documentary War Art of Shaun Gladwell - Messham-Muir, Kit (2014)
Shaun Gladwell is an Australian video installation artist whose practice is concerned with the bodily gesture and motion. In 2009, Gladwell was appointed an Official War Artist by the Australian War Memorial, and was sent to Afghanistan and the Middle East to create a body of work about the frontline experiences of Australian Defence Force personnel. This article examines the particular approach of Gladwell’s Official War Artist works. Other contemporary Australian artists dealing with war, such as Ben Quilty, George Gittoes and Wendy Sharp, tend to adopt a subjective documentary approach to war’s narratives of trauma, concentrating on weighty themes such as death, loss, and post-traumatic stress. In contrast,Gladwell’s war art actively resists both subjectivity and documentary. Unlike Quilty’s “humanist approach”, Gladwell avoids the political and emotional baggage inherent in images of war. Drawing from theorists Charles Green, Nicholas Croggon and Carolyn Christov-Bakargiev, who argue that Gladwell’s video works actively resist the narrative tendencies of the moving image, this paper suggests that Gladwell consciously resists the documentary inclinations of photographic and video media. His work also avoids narrative and, ultimately, resists articulating any subjective positionality, either his own or that of the soldiers he portrays.